Coconut Oil Heat Capacity - Bardan Bulaka; Syarifuddin Syarifuddin; Eko Harianto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Heat is energy transferred between a system and its surroundings due to the temperature difference that exists between them. Phase changes of coconut oil can be seen at temperatures between 20°C–100°C. To calculate the incoming heat using the equation Q = m.c.ΔT. Where Q in the experiment is calculated by the equation Q = V.I.t. So to calculate the specific heat of heat (c) = Q/(m.ΔT). The heat capacity is obtained from the equation C = m.c. The method in this practicum is used heater with AC current. The heater used has a voltage of 220 Volts, with a power of 350 Volts. Because the heating voltage is too large, a variable ac (variac) is used to lower the voltage. The voltage used is 20 volts. The material used is coconut oil which is labeled "Barco". The heater directly interacts with the oil. So that the oil can be directly heated homogeneously. Then it is bounded by adiabatic walls. The temperature in this study was controlled, ranging from 150C-500C. the heat of fusion of coconut oil at 28°C. After that, the liquid phase is above 28 °C to 63 °C. This is in accordance with the oil label which states that the melting temperature (melting) is around 26 °C. This difference is due to a leak or air entering the adiabatic wall.